A Case of 25 Year Old Dwarf with Classic Cockayne Syndrome - Mohammed, Fazle Rabbi; Chowdhury, FR; Nur, Zannatun; Shams, MZ; Alam, MB; Ahasan, HAMN (Journal of Medicine, 2010)
A 25 year old, short stature man of non-consanguineous parents, attended with acute respiratory tract infection along with progressive difficulties in walking, hearing and vision. He had the complaints of growth retardation, poor feeding, listless attitude and delayed milestones of development since one year of age. At presentation, he was non cooperative, IQ below 50; height and weight were below 5th percentile. He had progeria with enophthalmos, cataract, corneal opacity, miotic pupils, tremor, ataxia, in-coordination of movement, diminished tendon reflexes, unsteady gait, bilateral sensory neural deafness and hepatomegaly. Lateral skull X-ray showed cortical calcification. MRI of brain revealed bilateral dentate nucleus and basal ganglia calcification, generalized cerebral and cerebellar atrophy and ventricular dilatation. Typical clinical and imaging findings clinched the diagnosis of classic Cockayne Syndrome; which is a rare, autosomal recessive, DNA repair deficient, multisystem disorder. It has no cure and the prognosis is poor. Keywords: Classic Cockayne syndrome; Dwarfism; Basal ganglia calcification; Cerebral atrophy DOI: 10.3329/jom.v11i2.5470 J MEDICINE 2010; 11 : 186-188